Few-shot font generation via denoising diffusion and component-level fine-grained style - Liu, Yu; Ding, Yang; Khalid, Fatimah; Wang, Cunrui; Wang, Lei (Elsevier, 2025)
Few-shot font generation aims to create new fonts using a small number of style examples. It is increasingly gaining attention due to its significant reduction in labor costs. Existing methods rely on GAN-based image-to-image style-transfer frameworks, which are prone to training collapse and struggle to maintain consistency between character content and style. Moreover, they capture only the global style while overlooking fine-grained features of radicals, components, and strokes. To address these challenges, we propose a diffusion model-based image-to-image font generation method.We fully consider the component styles between content glyphs and reference glyphs, assigning appropriate fine-grained styles to content glyphs through a multi-character style aggregation module. Additionally, in order to better preserve the integrity of character structures during the denoising iteration process, we propose leveraging an offset-enhanced multi-head attention mechanism. This mechanism adaptively samples and embeds multi-scale glyph content features into the diffusion model. Comprehensive experiments demonstrate that our method outperforms existing font generation methods both qualitatively and quantitatively.